Discriminating climatological regimes in rainfall time series by using the Fisher-Shannon method - Pierini, Jorge Omar (2011)
The Fisher-Shannon (FS) information plane, defined by the Fisher information measure (FIM) and the Shannon entropy power (Nx), was robustly used to investigate the complex dynamics of 8 long monthly rainfall time series in central Argentina, recorded from 1860 to 2006. In the FS plane, the rainfall series seem to aggregate into three different clusters corresponding to three different climatological regimes in central Argentina. Our findings suggest the use of the statistical quantity defined by the FS information plane as a tool to discriminate among different climatological regimes.